2021
DOI: 10.1186/s12913-021-06155-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and its socio-demographic correlates in a tertiary public hospital in Nepal: a cross-sectional study

Abstract: Background Patient satisfaction is one proxy indicator of the health care quality; however, enhancing patient satisfaction in low-income settings is very challenging due to the inadequacy of resources as well as low health literacy among patients. In this study, we assess patient satisfaction and its correlates in a tertiary public hospital in Nepal. Methods We conducted a cross sectional study at outpatient department of Bhaktapur Hospital of Nepa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
27
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 26 publications
10
27
8
Order By: Relevance
“…This has earned acceptance to determine the standard of skilled delivery, reproductive care (2)(3)(4), and clinical practices. It helps healthcare management to develop policies to meet expectations in the course of improving healthcare delivery (7,8). This is by the WHO's definition of health as "not just the absence of illness or disease but a state of absolute physical, psychological, and general health" (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has earned acceptance to determine the standard of skilled delivery, reproductive care (2)(3)(4), and clinical practices. It helps healthcare management to develop policies to meet expectations in the course of improving healthcare delivery (7,8). This is by the WHO's definition of health as "not just the absence of illness or disease but a state of absolute physical, psychological, and general health" (6).…”
Section: Introductionmentioning
confidence: 99%
“…The satisfaction of postpartum mothers is the measure of their desired expectations, intentions, preferences, and experiences from skilled delivery (7,8,10,11). Skilled delivery is a service provided in a structured facility by a certified health worker who has been trained to be proficient in the services required to improve the lives of expectant mothers during labor and the postpartum period (2,12).…”
Section: Introductionmentioning
confidence: 99%
“…This study's findings indicated that, commonly, patients are satisfied with the health care services they got from the nurses at the clinics in contrast to other findings [13]. However, the findings indicated that there was no statistically significant difference between the mean patient satisfaction in terms of age, gender, educational status, employment status, number of clinic visits, the reason for the visit, and health status [14].…”
Section: Discussionmentioning
confidence: 92%
“…The relationship between satisfaction and socio-demographic/economic factors was reported by other studies elsewere. 36,37 The study finding also indicated a significant association between service characteristics (length of waiting time to see a provider) and women's satisfaction with screening services. Women who perceived waiting time as "medium" were nearly three times more likely to be satisfied than women who perceived waiting time as "long".…”
mentioning
confidence: 73%